ATP synthase from Trypanosoma brucei has an elaborated canonical F1-domain and conventional catalytic sites - Montgomery, Martin G; Gahura, Ondřej; Leslie, Andrew G W; Zíková, Alena; Walker, John E (Proceedings of the National Academy of Sciences of the United States of America, 2018)
The structures and functions of the components of ATP synthases, especially those subunits involved directly in the catalytic formation of ATP, are widely conserved in metazoans, fungi, eubacteria, and plant chloroplasts. On the basis of a map at 32.5-Å resolution determined in situ in the mitochondria of Trypanosoma brucei by electron cryotomography, it has been proposed that the ATP synthase in this species has a noncanonical structure and different catalytic sites in which the catalytically essential arginine finger is provided not by the α-subunit adjacent to the catalytic nucleotide-binding site as in all species investigated to date, but rather by a protein, p18, found only in the euglenozoa. A crystal structure at 3.2-Å resolution of the catalytic domain of the same enzyme demonstrates that this proposal is incorrect. In many respects, the structure is similar to the structures of F1-ATPases determined previously. The α3β3-spherical portion of the catalytic domain in which the three catalytic sites are found, plus the central stalk, are highly conserved, and the arginine finger is provided conventionally by the α-subunits adjacent to each of the three catalytic sites found in the β-subunits. Thus, the enzyme has a conventional catalytic mechanism. The structure differs from previous described structures by the presence of a p18 subunit, identified only in the euglenozoa, associated with the external surface of each of the three α-subunits, thereby elaborating the F1-domain. Subunit p18 is a pentatricopeptide repeat (PPR) protein with three PPRs and appears to have no function in the catalytic mechanism of the enzyme.
Keywords: Catalytic Domain; Models, Molecular; molekulární modely; Protozoan Proteins; Gene Expression Regulation, Enzymologic; katalytická doména; Protein Conformation; protozoální proteiny; Protein Subunits; regulace genové exprese enzymů; podjednotky proteinů; Trypanosoma brucei brucei; konformace proteinů; Mitochondrial Proton-Translocating ATPases; mitochondriální protonové ATPasy